Effect of the Japanese medical office system on job satisfaction, loyalty, engagement, and organizational commitment of medical practitioners: a survey of cardiologists in the acute care setting - Satoru Hashimoto; Yoshihiro Motozawa; Toshiki Mano (BMC, 2024)
Abstract Background In Japan, medical doctors have traditionally been assigned from university medical offices, under the medical office system. The present study examined the effects of the medical office system on job satisfaction, engagement, loyalty, and organizational commitment among cardiologists. Methods In this study, a survey of 156 cardiologists was conducted, from April 22, 2023, to May 21, 2023, to examine the effect of the medical office system on employee job satisfaction, employee engagement, and organizational commitment. Results Compared with the group that belonged to a medical office system (affiliated group, n = 117), the group that did not belong to a medical office system (non-affiliated group, n = 39) was affiliated to hospitals with a smaller number of beds. The results of the factor analysis showed that four types of hospital management styles were generated, namely, environment-, loyalty-building-, treatment-, and philosophy-oriented hospitals. There is an indication that the philosophy-oriented management style was adopted at the workplaces of the non-affiliated group. The treatment-oriented style also tended to be higher in the non-affiliated group than in the affiliated group. Furthermore, the non-affiliated group had higher organizational commitment, indicating that they were more likely to agree with the management philosophy set forth by hospital executives. Conclusion Although the medical office system did not affect job satisfaction, compared with medical doctors with the affiliated group, those with the non-affiliated group tended to work in hospitals that emphasized philosophy-oriented management, and they received moderate compensation while practicing in an environment suitable for their specialty. These results suggest that the medical office system makes it difficult for medical doctors to have high workplace loyalty, engagement, and commitment to the hospital to which they are dispatched.